Searching for periodic variations in radial velocities after the removal of orbital motions of spectroscopic binaries. (29th December 2020) - Katoh, Noriyuki; Itoh, Yoichi; Sato, Bun'ei
ABSTRACT: This study focuses on periodic variations of radial velocities (RVs) after removing the orbital motion of 33 spectroscopic binaries. The RVs were monitored from 2003 to 2012 and published in Katoh et al. (2013, AJ, 145, 41). Their RV precision was determined to be ∼10 m s −1 utilizing an I2 cell. We investigated the periodic variation using a generalzied Lomb–Scargle algorithm and found periodic variations in the residual velocities of seven binary systems. The residual-velocity variations are mostly generated by stellar activity rather than the orbital motion of a possible companion. For eight binaries, we found significant evidence of a second signal, with velocity dispersions greater than three times the RV uncertainty. We find these residual-velocity variations inconsistent with a Doppler signal induced by the orbital motion of an unknown component. For the remaining 18 binaries, we did not detect significant variations of residual-velocity.